1999
DOI: 10.1159/000016677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static Electromagnetic Fields on Chick Embryo Pineal Gland Development

Abstract: The effects of static electromagnetic fields on the development of the chick embryo pineal gland were studied. A total of 144 fertilized White Leghorn eggs were sacrificed after 5, 10 and 15 days of incubation. The stage of development was determined in all embryos using the Hamburger and Hamilton method [J Morphol 49: 88–92, 1951]. The various morphometric parameters (diameter and distance of the pineal gland and its lumen) were measured on serial 7-μm-thick sections. The data were obtained in a morphometer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Chicken and mosquito were also used to study the effects of SMF on embryonic development, which all showed obvious effects. For example, Jove et al [1999] reported that chick embryos exposed to 18 or 36 mT homogeneous SMFs generated by electromagnets tended to have a more developed pineal gland than controls. Ruggiero et al [2004] placed chicken embryos in the center of the sector magnetic resonance tomograph scanner for 3 h, where the SMF intensity reached 0.2 T (permanent magnet, inhomogeneous), and found that the angiogenesis on the chorioallantoic chorion of chicken embryo was significantly inhibited.…”
Section: In Vitro Studies Of Smfs On Early Embryonic Developmentmentioning
confidence: 99%
“…Chicken and mosquito were also used to study the effects of SMF on embryonic development, which all showed obvious effects. For example, Jove et al [1999] reported that chick embryos exposed to 18 or 36 mT homogeneous SMFs generated by electromagnets tended to have a more developed pineal gland than controls. Ruggiero et al [2004] placed chicken embryos in the center of the sector magnetic resonance tomograph scanner for 3 h, where the SMF intensity reached 0.2 T (permanent magnet, inhomogeneous), and found that the angiogenesis on the chorioallantoic chorion of chicken embryo was significantly inhibited.…”
Section: In Vitro Studies Of Smfs On Early Embryonic Developmentmentioning
confidence: 99%